Uncertainty and Quantity Adjustment in The General Theory - Rodríguez Herrera, Adolfo (2009)
Robert Clower develops an interpretation of Keynes’ criticism of capitalist economy, by which uncertainty explains the systems’ inability to reach equilibrium in all markets, and specially in the labor market. Non-compliance with the main neoclassical assumption, perfect information, makes interest rate lose its regulating role and the system is unable to adjust itself via price movements. In presence of unemployment, individual revenue is no more the result of an optimizing process led by economic agents, and any external shock provokes a quantity adjustment called by Keynes “the multiplier effect”, which leaves the labor market without instruments to reach equi- librium.